PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MENANGANI EKSPLOITASI PEKERJA ANAK DI PERTAMBANGAN KOBALT REPUBLIK DEMOKRATIK KONGO 2018-2024 - Firmansyah, Aditama Novindri; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Child labor exploitation in cobalt mining in the Democratic Republic of Congo (DRC) represents a global paradox where the green energy transition in developed countries depends on supply chains supported by the exploitation of up to 40,000 children in hazardous conditions. Extreme poverty reaches 72.9% of the population, weak law enforcement, and the absence of state protection functions make the DRC case the most severe in the world, opening space for intervention by the International Labour Organization (ILO) as an international actor with a specific employment mandate. This study employs a qualitative method with a literature review approach and is grounded in the international organization theory of Barnett and Finnemore, which positions the ILO as an autonomous actor with normative and epistemic power, complemented by a constructivist perspective to understand the process of socialization of norms prohibiting child labor. Through this framework, the ILO is analyzed based on three main functions: creating and disseminating global norms, overseeing state compliance through technical oversight mechanisms, and filling institutional gaps through the COTECCO and GALAB programs. The findings show that the ILO successfully transformed the discourse on child labor from a family economic issue to a serious human rights violation through harmonizing national law with Conventions No. 138 and No. 182. The ILO developed the Child Labour Monitoring and Remediation Systems (CLMRS), withdrew 1,527 children from mines, prevented 6,464 children from entering child labor, and strengthened government institutional capacity and family economic support. Effectiveness has been qualitatively proven in improving child protection conditions in intervention areas, although limited by political instability, weak law enforcement, and the complexity of global cobalt supply chains. Keywords: International Labour Organization, International Organization, Child Labor, Cobalt Mining, Democratic Republic of The Congo